FENOMENA SALAFI DI KALIMANTAN SELATAN - Syahbana, Takdir Ali (Fakultas Ushuluddin dan Humaniora IAIN Antasari, 2015)
Salafi is one of Islamic movement which have spread around the world. This movement initiates to purify IslamicÂ doctrine from what it called bidâah. It has been currently in South Kalimantan for several years. In fact, the movementhas several places that be the center of its teaching. Data showed that Ustadz Aiman and his brother introduce it atÂ the first in 2001. Since that time, Salafi has developed and has had many followers. In several big cities of SouthÂ Kalimantan district, such as Banjarmasin, Martapura, and Barabai, Salafi built some mosques and used it as itsÂ learning and teaching center. This writing discussed about the development of Salafi movement in South Kalimantan.Â It will be reviewed about Salafiâs methods in introducing and teaching its doctrine to the people of South Kalimantan.